Mushroom Cultivation for Farmer Existence: A Normative and Economic Review - Iqbal Kurniawan; M Muthoifin; Zafran Akhmadery Arif; Hamzah Assuudy Lubis; Hardin La Ramba; Muhamad Subhi Apriantoro; Ahmad Imam Hambali; Jihan Husna Srifyan (Walidem Institute and Publishing, 2023)
The purpose of the study is to determine the business of ear mushroom cultivation in increasing farmers' income from a normative and economic perspective. Research site in Tawangmangu Karanganyar. The subject of this study is business actors and employees of the Ear Mushroom House in Tawangmangu, while the object of this study is entrepreneurial opportunities for ear mushroom cultivation based on Sharia glasses. The methods used are interview and observation techniques. The data analysis used is qualitative research. The results of the research show that Mitra Mandiri's business from a Sharia perspective is very prospective and Sharia-compliant, because the acquisition obtained is greater than the resources used, and the implementation of planting does not deviate from the rules prohibited in Islam. This mushroom business is very prospective, but there are several obstacles in cultivating mushroom houses, namely many failed seeds, many pests, long production processes, uneven marketing, and lack of human resources. Although there are obstacles, all obstacles can be solved.